Human brains have shrunk: the questions are when and why - DeSilva, Jeremy; Fannin, Luke; Cheney, Isabelle; Claxton, Alexander; Ilieş, Iulian; Kittelberger, Jessica; Stibel, Jeff; Traniello, James (Frontiers in Ecology and Evolution, 2023)
Human brain reduction from the Late Pleistocene/Holocene to the modern day is a longstanding anthropological observation documented with numerous lines of independent evidence. In a recent study (DeSilva et al., 2021; Front. Ecol. Evol.), we analyzed a large compilation of fossil and recent human crania and determined that this reduction was surprisingly recent, occurring rapidly within the past 5,000 to 3,000 years of human history. We associated such a change as a consequence of population growth and cooperative intelligence and drew parallels with similar evolutionary trends in eusocial insects, such as ants. In a reply to our study, Villmoare and Grabowski (2022; Front. Ecol. Evol.) reassessed our findings using portions of our dataset and were unable to detect any reduction in brain volume during this time frame. In this paper, responding to Villmoare and Grabowski’s critique, we reaffirm recent human brain size reduction in the Holocene, and encourage our colleagues to continue to investigate both the timing and causes of brain size reduction in humans in the past 10,000 years.